Antimycoplasma properties and application in cell culture of surfactin, a lipopeptide antibiotic from Bacillus subtilis. - Vollenbroich, D (1997)
Surfactin, a cyclic lipopeptide antibiotic and biosurfactant produced by Bacillus subtilis, is well-known for its interactions with artificial and biomembrane systems (e.g., bacterial protoplasts or enveloped viruses). To assess the applicability of this antiviral and antibacterial drug, we determined the cytotoxicity of surfactin with a 50% cytotoxic concentration of 30 to 64 microM for a variety of human and animal cell lines in vitro. Concomitantly, we observed an improvement in proliferation rates and changes in the morphology of mycoplasma-contaminated mammalian cells after treatment with this drug. A single treatment over one passage led to complete removal of viable Mycoplasma hyorhinis cells from various adherent cell lines, and Mycoplasma orale was removed from nonadherent human T-lymphoid cell lines by double treatment. This effect was monitored by a DNA fluorescence test, an enzyme-linked immunosorbent assay, and two different PCR methods. Disintegration of the mycoplasma membranes as observed by electron microscopy indicated the mode of action of surfactin. Disintegration is obviously due to a physicochemical interaction of the membrane-active surfactant with the outer part of the lipid membrane bilayer, which causes permeability changes and at higher concentrations leads finally to disintegration of the mycoplasma membrane system by a detergent effect. The low cytotoxicity of surfactin for mammalian cells permits specific inactivation of mycoplasmas without significant deleterious effects on cell metabolism and the proliferation rate in cell culture. These results were used to develop a fast and simple method for complete and permanent inactivation of mycoplasmas in mammalian monolayer and suspension cell cultures.